Revisiting Disciplinary Control in Secondary Schools: The Issue of Corporal Punishment in Calabar South Local Government Area of Cross River State, Nigeria - Ukpabio, Godfrey E.; Usen, Mbon F.; Etor, Comfort (Mediterranean Journal of Social Sciences, 2019)
This research investigated the administration of corporal punishment as a disciplinary control mechanism in secondary schools of Nigeria with particular reference to Calabar South Local Government Area of Cross River State, Nigeria. The concept of corporal punishment as a disciplinary control mechanism with the social issues associated with it was discussed. Three hypotheses were formulated to guide the study which adopted survey research design. A questionnaire titled: "Corporal Punishment and Disciplinary Control Questionnaire" (CPDCQ)was the instrument for data collection. The simple random sampling technique was used in selecting 200 teachers for this study. The data obtained was analyzed using Independent t-test and Analysis of Variance (ANOVA) test statistics at 0.05 level of significance. The findings of the study showed that there is a significant difference in the administration of corporal punishment as a disciplinary control mechanism in secondary schools of Calabar South Local Government Area of Cross River State based on teachers’ gender and teachers’ teaching experience. The findings also revealed that there is a significant difference in the administration of corporal punishment as a disciplinary control mechanism of teachers working in public or private secondary schools in the study area. It was recommended among other things that since appropriate application of corporal punishment is associated with disciplinary control in these schools, a mechanism be put in place to guide usage and to check abuses.